Enhancement of thermomechanical properties of sulfur-rich polymers by post-thermal treatment. Issue 8 (31st January 2023) - Han, Nara; Cho, Woongbi; Hwang, Jae Hyuk; Won, Sukyoung; Kim, Dong-Gyun; Wie, Jeong Jae
Abstract : A simple and facile processing strategy to enhance the thermomechanical properties of sulfur-rich polymers has been reported. Abstract : Recently, sulfur-rich polymers have been applied in various fields including energy storage, mercury removal, and infrared (IR) optics. However, sulfur-rich polymers typically exhibit insufficient thermomechanical properties for practical applications. Herein, we systematically investigate the effects of thermal treatment on the thermomechanical properties, represented by the glass transition temperature ( T g ) and storage modulus, of sulfur-rich polymers prepared by inverse vulcanization with 70 wt% elemental sulfur (S) and 30 wt% divinylbenzene (DVB). The thermal treatment was conducted at three different temperatures (110, 140, and 170 °C) for six different times (1, 2, 6, 12, 24, and 48 h). During the thermal treatment, the thermomechanical properties of poly(sulfur70 - random -DVB30 ) [poly(S70 - r -DVB30 )] increased owing to the thermal degradation of small molecules, including sulfur oligomers and thermally degraded DVB, which acts as a plasticizer. However, excessive thermal treatment induced a deterioration in thermomechanical properties owing to thermal degradation. By systematic investigation of the thermal treatment, the storage modulus of poly(S70 - r -DVB30 ) could increase from 3 GPa to 4 GPa.